Single-step lipase-catalyzed functionalization of medium-chain-length polyhydroxyalkanoates - Gumel, A.M.; Annuar, M.S.M.; Heidelberg, T. (Society of Chemical Industry, 2013)
BACKGROUND: Functionalization of aliphatic biopolymers such as bacterial polyhydroxyalkanoates (PHA) using biologically active hydrophilic moieties like sugars helps to improve the hydrophilicity and biodegradability of the biomaterial. RESULTS:Theeffects of reaction variables reaction time, temperature,enzyme concentration and substrate ratio on reaction rate and yield in the synthesis of poly(1’-O-3-hydroxyacyl-sucrose) using Candida antarctica lipase B (EC 3.1.1.3)were studied. Using H2O2 as micro-initiator, enzyme-mediated synthesis yielded reaction rate, vapp of 0.076 x 10−5 mol L−1 s−1. The biodegradability of the functionalized polymer was observed to increase by 1.5 fold compared with the non-functionalized material apart from showing better compostability. Increasing the reaction temperature (>50◦C), enzyme concentration (>15 g L−1) and reactant ratio (w/w) of sucrose:PHA (>2) did not increase further the rate or yield. The sucrose-functionalized mcl-PHAwas characterized with respect to the non-functionalized material. CONCLUSIONS: Novozym 435 can be used effectively to synthesize poly(1’-O-3-hydroxyacyl sucrose) in micro-aqueous medium bypassing the need for chemo-synthetic steps. The synthesized biomaterials have potential applications in biomedical and industrial niches